Порівняльний аналіз застосування пліс і мікроконтролерів в системах радіолокації - Сєріков, А. О.; Пугач, К. О.; Свид, І. В. (ХНУРЕ, 2023)
This report will compare FPGAs and microcontrollers for their performance in radar systems, describing their characteristics and properties. The purpose of the report is to establish which of these components are more effective in radar systems and to determine their optimal field of use.
Keywords: ПЛІС; мікроконтролер; система радіолокаційна